Factoring with Pell conics - Rasa Šleževičienė (Lietuvos Matematikos Rinkinys)
In the paper the Pell conics method for factoring integers, based on observations of Lemmermeyer [2, 3], is presented explicitly. Moreover, a similar algorithm for factoring polynomials over finite fields is given.